Association of Copy Number Variation at Intron 3 of HMGA2 With Navel Length in Bos indicus - Aguiar, Tamíris Sayuri; Torrecilha, Rafaela Beatriz Pintor; Milanesi, Marco; Utsunomiya, Adam Taiti Harth; Trigo, Beatriz Batista; Tijjani, Abdulfatai; Musa, Hassan Hussein; Lopes, Flávia Lombardi; Ajmone-Marsan, Paolo; Carvalheiro, Roberto; Neves, Haroldo Henrique de Rezende; do Carmo, Adriana Santana; et al. (Frontiers in Genetics, 2018)
Navel injuries caused by friction against the pasture can promote infection, reproductive problems and costly treatments in beef cattle raised in extensive systems. A haplotype-based genome-wide association study (GWAS) was performed for visual scores of navel length at yearling in Nellore cattle (Bos indicus) using data from 1298 animals and 503088 single nucleotide polymorphism (SNP) markers. The strongest signal (p = 1.01 x 10-9) was found on chromosome 5 spanning positions 47.9 - 48.2 Mbp. This region contains introns 3 and 4 and exons 4 and 5 of the high mobility group AT-hook 2 gene (HMGA2). Further inspection of the region with whole genome sequence data of 21 animals revealed correlations between counts of the significant haplotype and copy number gains of a 6.2 kbp segment of intron 3 of HMGA2. Analysis of genome sequences from five African B. indicus and four European Bos taurus breeds revealed that the copy number variant (CNV) is indicine-specific. This intronic CNV was then validated through quantitative polymerase chain reaction (qPCR) using Angus animals as copy neutral controls. Importantly, the CNV was not detectable by means of conventional SNP-based GWAS or SNP probe intensity analyses. Given that HMGA2 affects the expression of the insulin-like growth factor 2 gene (IGF2) together with the pleomorphic adenoma gene 1 (PLAG1), and that the latter has been repeatedly shown to be associated with quantitative traits of economic importance, these findings highlight the relevance of the HMGA2-PLAG1-IGF2 pathway to cattle breeding.